2021
DOI: 10.33448/rsd-v10i8.17278
|View full text |Cite
|
Sign up to set email alerts
|

Brasil: tabagismo e consumo de bebida alcoólica nos últimos dez anos (vigitel) e o papel do Cirurgião-Dentista na prevenção do câncer bucal

Abstract: O presente trabalho objetivou discutir a frequência estimada do tabagismo e consumo de bebida alcoólica nos últimos 30 dias, por sexo, faixa etária e grau de escolaridade no Brasil nos últimos dez anos, e analisar o papel do cirurgião-dentista da atenção básica frente aos principais fatores de risco para o câncer bucal. Foi realizado por meio de um estudo ecológico com dados do VIGITEL entre os anos de 2009 e 2019, e que teve como resultado uma diminuição positiva no número de tabagistas, decrescendo de 15,5 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0
3

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 10 publications
1
1
0
3
Order By: Relevance
“…Extensive literature demonstrates that smokers have worse oral health, represented by a greater number of periodontal problems, a greater number of missing dental elements, higher prevalence of oral cancer, among other diseases (Pereira et al, 2014;Dietrich et al, 2007;Ahsan et al, 2020;Alves et al, 2017;Lopes et al, 2021;Santos et al, 2022), which partially corroborates the findings of this study, since it identified, for example, a worse periodontal condition among smokers.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Extensive literature demonstrates that smokers have worse oral health, represented by a greater number of periodontal problems, a greater number of missing dental elements, higher prevalence of oral cancer, among other diseases (Pereira et al, 2014;Dietrich et al, 2007;Ahsan et al, 2020;Alves et al, 2017;Lopes et al, 2021;Santos et al, 2022), which partially corroborates the findings of this study, since it identified, for example, a worse periodontal condition among smokers.…”
Section: Discussionsupporting
confidence: 87%
“…Tobacco is also associated with the occurrence of deleterious effects on oral health. Several previous studies demonstrate that smokers have a higher risk of tooth loss (Pereira et al, 2014;Dietrich et al, 2007), higher prevalence of periodontal diseases, dental caries and leukoplasia (Ahsan et al, 2020;Santos et al, 2022) as well as a higher risk of developing oral squamous cell carcinoma (Alves et al, 2017;Lopes et al, 2021). On the other hand, the literature is scarce on a possible impact of smoking on oral health-related quality of life (OHRQoL) (Bakri et al, 2018;Sagtani et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Em relação a várias pesquisas realizadas na literatura, foram observados diferentes entendimentos dos DEFs, sendo que suas composições e misturas, podem provocar danos à saúde bucal e sistêmica, seus efeitos nocivos não diferem muito quando comparados com os efeitos do uso tradicional do tabaco, correlacionando esses fatores, observa-se que é alta a influência do consumo no desenvolvimento do câncer de boca (Lopes et al, 2021).…”
Section: Diversos Compostos Presentes No Refil Dosunclassified
“…O consumo de bebida alcoólica é um fator de risco para o câncer bucal que se utilizado em conjunto com substâncias relacionadas as práticas tabagistas podem aumentar o potencial cancerígeno, assim, estima-se que o consumo exagerado de álcool seja responsável por 5,2% das mortes por câncer em homens e 1,7% em mulheres (Lopes et al, 2021;Sant'ana et al, 2021).…”
Section: Etilismounclassified
See 1 more Smart Citation